Adaptación del Inventario de Estrés Académico SISCO SV al contexto de la crisis por COVID-19 - Alania Contreras, Rubén Darío (2020)
The research objective was adapted SISCO SV Academic Stress Inventory to the context of the crisis by COVID-19, the basic type study, descriptive level, non-experimental design, simple descriptive cross-sectional; For content validation, a sample of 20 experts in psychology, education, research and statistics will be consulted, who will be provided with a generic validity sheet and a specific validity sheet; They are also needed with a sample of 151 students from four universities in the Junín region of Peru, to whom they must administer the adapted inventory of academic stress SISCO SV de Barraza (2018), to assess the validity of construction and reliability. The results indicated by the instrument present generic and content-specific validity according to the Aiken coefficient of concordance V, with indices greater than 0.75 (excellent validity); likewise, construct validity was determined with corrected Pearson correlation coefficients greater than 0.2, between sufficient validity (0.2 to 0.34), good (0.35 to 0.44), very good (0.45 to 0.54) and excellent (0.55 to 1); the reliability of the symptoms instrument the Cronbach's alpha internal consistency coefficient of 0.9248 for the stressors dimension, 0.9518 for the symptoms dimension and 0.8837 for the coping strategies dimension (excellent reliability). It was concluded that the SISCO SV Academic Stress Inventory, adapted to the context of the crisis by COVID-19, is valid and reliable.